'Babylon': Then, Now and 'Not Yet': Anti-Roman Rhetoric in the Book of Revelation. (February 2013) - Diehl, Judy
This article is the third and final essay in a three-part series concerned with an analysis of current scholarship and anti-imperial rhetoric in the writings of the New Testament. The focus of this article is on the challenges and the inspiration of the book of Revelation. While Revelation may be considered to be the most unambiguous and blatant example of confrontation between the early Christians and the Roman Empire in the New Testament, a diversity of opinions survives as to how modern readers should understand and apply John's apocalyptic literature. Does this book have something to say to readers today about the concepts of 'empire', colonialism and imperialism? We begin with a reflection on ancient interpretations of the text of Revelation, which are foundational to today's interpretations, and lend support to the existence of anti-imperial rhetoric found in this cryptic document. Consideration is given to numerous current scholarly approaches, historical, theoretical and literary, with select examples from the book of Revelation for a greater understanding of the text.